Localization Principle for Triebel-Lizorkin Spaces on Spaces of Homogeneous Type - Yang, Dachun (Revista Matemática Complutense, 2004)
The author establishes the localization principle for the Triebel-Lizorkin spaces on spaces of homogeneous type.